Simulasi Pengadaan Usaha Turunan Berbasis Buah dan Limbah Salak Pondoh untuk Meningkatan Pendapatan Industri Salak Pondoh di Kabupaten Sleman - Muhammad Prasanto Bimantio; Dian Pratama Putra (AGROINTEK, 2021)
The high production of salak pondoh in Sleman Regency is not in line with the welfare of the farmers. The farmers receive a low price during the main harvest season, where the selling price per kilogram drops below the cost of production, so that the profit margins of farmers are not met. Abundant production during the main harvest and characteristics of perishable fruit are the cause of this problem, so that most farmers sell their crops to the nearest traders. This condition makes the bargaining position of farmers weak and the price determined by the traders, thus impacting on the decline in their welfare level. The purpose of this study is to formulate the salak pondoh business model in Sleman Regency in the form of dynamic simulations to carry out various scenarios of procuring business products based on raw materials in the form of fruit and waste from salak pondoh. The results of this simulation are expected to provide an alternative picture of solutions, steps, and conditions for academics, business people, and government in the form of a simulation template for each scenario. Data collection was carried out through direct observation to the salak pondoh place of business in Sleman Regency, brainstorming, interviews with related parties such as the salak pondoh association and the Sleman District Agriculture Office, and secondary data documentation on research topics. Scenarios of derivative business procurement (fruit and waste-based raw materials) provide a significant increase in income compared to business as usual business conditions, ranging from 4% - 44% in various fractions tested and up to 293% in extreme conditions and able to reduce the number of unemployed in Sleman Regency. The scenario of supplying derivative business made from pondoh salak fruit provides a significant increase in income compared to procurement of derivative business made from pondoh salak plant waste. It takes a probability value of sales of derivative products of more than 48.97% so that the revenue value from the business procurement scenario is greater than business as usual